A Jocic-type approach for a practical and scalable synthesis of pyrrolonaphthoxazepine (PNOX)-based potent proapoptotic agents. Issue 51 (19th December 2018) - Federico, Stefano; Khan, Tuhina; Relitti, Nicola; Chemi, Giulia; Brindisi, Margherita; Brogi, Simone; Novellino, Ettore; Zisterer, Daniela M.; Campiani, Giuseppe; Gemma, Sandra; Butini, Stefania
Graphical abstract: Highlights: Jocic-type protocol for the construction of the pyrrolonaphthoxazepine (PNOX) core. A variety of reaction conditions were investigated. The novel route significantly improved overall yields to obtain PNOX-based compounds. The novel route was extended to the preparation of 1, 4-benzoxazinone templates. Abstract: We developed a Jocic-type protocol for the construction of the pyrrolonaphthoxazepine (PNOX) core. After an initial investigation based on the isolation of a trichloromethyl carbinol derivative, we shifted our attention towards a multicomponent single-step protocol. Screening of a variety of bases and solvents led to the identification of the optimum conditions for the preparation of the key α-aryloxy carboxylic acids to undergo intramolecular cyclization. The novel chemical route significantly improved overall yields for the preparation of PNOX-based compounds and was successfully extended to the preparation of 1, 4-benzoxazinone-based templates.